The Use of Intraoperative Extracorporeal Membrane Oxygenation in Lung Transplantation: Initial Institutional Experience - Atakan Erkılınç; Mustafa Vayvada (Brazilian Journal of Cardiovascular Surgery, 2022)
ABSTRACT Introduction: Lung transplantation is the final treatment option for end-stage lung disease, and extracorporeal membrane oxygenation (ECMO) is increasingly being used during lung transplantation. Objective: The present study aimed to review our initial experience with patients who underwent lung transplantation with or without ECMO since the implementation of the lung transplantation program at our center. Methods: Data were prospectively collected on all patients between December 2016 and December 2018. Patients undergoing ECMO as a bridge to lung transplantation were excluded. Results: A total of 48 lung transplants were performed, and ECMO was used in 29 (60.4%) cases. Twenty (83%) patients were female. The median age was 48.5 (range, 14-64) years. The most common indications were idiopathic interstitial pneumonia in 9 (31%) patients, chronic obstructive pulmonary disease in 7 (24.1%) patients, and bronchiectasis in 6 (20.7%) patients. Sequential bilateral lung transplantation was performed in all patients. The 30-day mortality was 20.6% (6/29) for patients with ECMO, however, it was 10.5 (2/19) for patients without ECMO (P=0.433). The median length of stay in the intensive care unit (ICU) was 5 (range, 2-25) days. The ECMO weaning rate was 82.8% (24/29). One-year survival was 62.1% with ECMO versus 78.9% without ECMO, and the 3-year survival was 54.1% versus 65.8%, respectively (P=0.317). Conclusions: ECMO is indicated for more severe patients who underwent lung transplantation. The use of ECMO provides adjuvant support during surgery and the mortality rate is acceptable. Survival is also as similar as non-ECMO patients. ECMO is appropriate for critically ill patients.